Treatment of cows with liver pathology using a liposomal drug based on extract from the fruits of Silybum marianum - Vlizlo, V.; Prystupa, O.; Slivinska, L.; Gutyj, B.; Maksymovych, I.; Chernushkin, B.; Leno, M.; Rusyn, V.; Shcherbatyy, A.; Lychuk, M. (Regulatory Mechanisms in Biosystems, 2024)
After labor, dairy cows are often diagnosed with fatty liver disease. The objective of our study was to identify the efficacy of a liposomal drug based on extract from seeds of Silybum marianum (L.) Gaertn., including tocopheryl acetate, lecithine, squalene, and Twin-80, which was intramuscularly administered to dairy cows to recover the functional state and structure of the liver from the disorder. The experiment involved clinically healthy cows and cows suffering disorders in the main functions and the structure of the liver. The sick cows were treated with intramuscular injections of the drug. Three-time administration of the liposomal drug, with two days interval between each dose, improved the functional condition and the structure of the damaged liver. Biochemical assays of blood of the cows after treatment revealed improvement of the bile-forming and bile-removing functions of the liver, and also removal of cholestasis, as evidenced by decreased concentrations of uric acids, total and conjugated bilirubin, and lower activity of gamma-glutamyl transpeptidase in serum. Intramuscular injections of the drug in the sick animals reduced the activities of the hepatospecific mitochondrial enzyme glutamate dehydrogenase in the blood serum, and also the indicatory enzymes aspartate aminotransferase and alanine aminotransferase, indicating recovery of the structure of hepatocytes and cessation of cytolysis. After treatment, the sick cows were observed to have upward tendencies in albumin and glucose, which may be interpreted as recovery of the protein-synthesizing and carbohydrate functions of the liver. However, three-time intramuscular injection of the S. marianum-based liposomal drug did not lead to complete recovery of the functions and the structure of hepatocytes in the cows suffering fatty liver disease, and therefore further research should be carried out, with longer and more complex therapeutic approaches.